Development of the Technology of PIXE Analysis - ISHII, Keizo (Advances in X-Ray Chemical Analysis, Japan, 2019)
When charged particles collide with atoms, atomic inner shell electrons are ionized and then characteristic X-rays are emitted. This phenomenon is called Particle Induced X-ray Emission: PIXE. Since the production cross-sections of characteristic X-rays in PIXE is very large, PIXE can be applied to trace element analysis and uranium from sodium can be simultaneously analyzed with the sensitivity of ppb. Two dimensional distributions for each element can be obtained by scanning ion beams on the surface of sample. The use of micro beams enables to investigate elements inside a cell: Micro-PIXE analysis. A micron size point source of monochromatic X-ray is made by irradiating a metal target with micro-beams and can be used to an X-ray CT with the spatial resolution of 1 μm: Micron X-ray CT. Three dimensional distributions of elements in the inside of sample with 100 μm size can be non-destructively obtained using absorption edges for each element. The PIXE analysis is now applied to medicine, biology, fisheries science, agriculture, geology, petrology, environmental problems, archeology, resource search, material science, chemistry, astrophysics, earth science, criminal investigation, food inspection etc. To investigate the radioactive cesium contamination of foods and soil by the Fukushima Daiichi Nuclear power plants accidents, Micro-PIXE and Micron X-ray CT were useful especially in rice grain and in clay, respectively.